A New Guide for the Arthroscopically Assisted Latarjet Procedure. Issue 1 (January 2021) - Imai, Shinji
Abstract : Background: The Latarjet procedure is a commonly used treatment for recurrent shoulder instability. However, its neurological complication rate has been reported to be as high as 10%. During the Latarjet procedure, the neurovascular structures are relocated inferiorly and medially. I hypothesized that the risk of nerve injury would be reduced by assisting the inferior-medial relocation of the neurovascular structures intraoperatively. Methods: Seventeen consecutive patients with shoulder instability accompanied by glenoid bone loss were treated with an all-arthroscopic Latarjet procedure assisted by the novel low-profile SaSumata (SS) guide. The SS guide is inserted through a portal made above the coracoid process and is attached to the coracoid process by 2 pre-fix screws (i.e., temporary pre-fixation screws). Unlike previous techniques, the SS guide is not shuttled from 1 portal to the other to redirect the bone graft from the donor site to the recipient site; instead, it remains attached to the graft throughout the procedure. The SS guide brings the coracoid graft along an inferior-medial trajectory, pushing aside the neurovascular structures with the help of a switching stick. Owing to its semicircular pronged head, the SS guide holds the graft until the pre-fix screws are exchanged with permanent screws. All patients were clinically assessed and underwent computed tomography (CT) scans. Results: This maneuver was performed arthroscopically in 17 patients, with no conversion to open surgery and no neurological injuries. No patient had recurrence of dislocation after follow-up for a minimum of 24 months. The mean Subjective Shoulder Value was 87.5% ± 11.7%. The mean Rowe score was 88 ± 15.7. The bone block was optimally positioned between 3 o'clock and 5 o'clock and was flush with the glenoid facet in 16 of the 17 patients. There was 1 fracture of the bone block. The mean operation time after the first 5 patients was 125 ± 23 minutes. Conclusions: The SS guide was a useful tool for performing the arthroscopically assisted Latarjet procedure for recurrent anterior shoulder instability, with good functional results. Level of Evidence: Therapeutic Level IV . See Instructions for Authors for a complete description of levels of evidence.